Thermo-mechanically coupled modelling of a single-asperity scratch on an isotropic isotactic polypropylene surface. (January 2020) - Kershah, Tarek; Looijmans, Stan F.S.P.; Anderson, Patrick D.; van Breemen, Lambèrt C.A.
Abstract: Isotactic polypropylene (iPP) is a low cost semi-crystalline polymer that is easy to process, has a wide variety in properties and is, therefore, used in many applications. Many of these applications require enhanced wear-resistance to prolong the lifetime of the product. Essential is to first investigate the intrinsic response of the material in order to describe its friction and wear response. In this respect, a hybrid experimental-numerical approach is used to couple the intrinsic response to the single-asperity scratch response. The numerical model used is a 3D elasto-viscoplastic model based on the Eindhoven Glassy Polymer (EGP) model. For the first time a coupled thermo-mechanical EGP model is implemented in a Finite Element Method (FEM)-framework. The model is capable of accurately describing the intrinsic response of the material, which opens the door to qualitatively and quantitatively describe its frictional response and understand the damage formation mechanism (i.e. the initiation of wear). In this study, α- and β-phase iPP are studied. We show that the difference in the intrinsic response between the two phases has a significant influence on the friction and wear response. Moreover, a stick-slip phenomenon is proven to be the main responsible for the damage mechanism observed. The observed periodic "fish-scale" damage pattern results from periodic changes in resistance during the tip movement. A relation between the polymer intrinsic response and the damage formation mechanism is established. The influence of the applied load and scratch speed on damage formation is investigated as well. Graphical abstract: Image 1 Highlights: A 3D viscoelastic constitutive model is used to perform FEM scratch simulations. Viscoelasticity of polymers enhances the scratch resistance at high sliding speeds. A fraction of the work done by the driving stress in polymers is dissipated into heat. Strain hardening resists damage formation and enhances wear resistance.